Use of Learning to Read Methods Without Spelling in Early Childhood Reading - Yusnita, Novi Cynthia; Dara Aisyah (Outline Publisher, 2025)
The problem that occurs in this study is that children often spell when reading a word or text. This of course will take a long time to read and become a habit when they enter further education. The purpose of this study was to determine the use of learning to read without spelling in early childhood. The research method used is descriptive qualitative research that is describing something that happens through the observations that have been made. The subjects in this study were early childhood, parents and tutors at Rumah Pintar Alamanda. The data collection technique used was observation of children and interviews with parents and tutors as well as documentation. Based on the results of the research and analysis that has been carried out, it appears that children are better at recognizing letters, vocabulary and connecting words at the beginning of reading by using the learning method to read without spelling. This is proven when the child is able to name the letters intended by the teacher. So that the use of the method of learning to read without spelling can help children in beginning reading in early childhood. Several things were done in this study, namely: (1) Introducing letters in a different way; (2) Introducing syllables; (3) Reading various syllables; (4) Read together. All of these activities are carried out under the direction and guidance of the tutor so that children can be even better at beginning